Pelatihan Akuntansi Rumah Tangga di Desa Pongongaila Kecamatan Pulubala Kabupaten Gorontalo - Juniaty Ismail (Komunal Jurnal Pengabdian Masyarakat, 2022)
Household Accounting is simply recording household expenses and expenses in a certain period, usually done every month. Partners in this community service activity are the Community in Pongongaila Village, Pulubala District, Gorontalo Regency, Gorontalo Province who on average have a livelihood as farmers and also karawo craftsmen (typical handicrafts of the Gorontalo region). But from some discussions conducted with some housewives who became participants during community service activities, it was clear that they did not know how to plan and manage their finances properly. So it is necessary to hold training related to this simple bookkeeping. After this training, participants gained additional knowledge and important information about household accounting in family life and how simple profiteering of income and expenses in family daily activities, how to prioritize between needs and desires, how to manage income to slip 2.5% zakat in it, to make decisions that are beneficial to the family.